Determinan proses keputusan pembelian online di kalangan konsumen Muslim pengguna Shopee: Kepercayaan sebagai variabel mediasi - Selamat Muliadi; Sri Ndaru Arthawati; Rini Oktavera; Willson Gustiawan; Wira Pramana Putra (Jurnal Manajemen Maranatha, 2024)
Every e-commerce company must be keen to see the opportunity to grow and effectively develop new innovations in the face of such fierce competition in order to keep customers from moving and to continue doing business with the company. One strategy to grow the current buying and selling industry quickly is to sell products online on social media and e-commerce platforms. This study aims to analyze and examine the factor influencing of Big Ramadan Sale, service quality, and online customer review on online purchase decision process with the trust as a mediating variable in Shopee application users. The quantitative and regression analysis were used as the research method in this study. The sample was obtained using a purposive sampling method and 110 respondents as a sample source was distribution online questionnaires via WhatsApp to Shopee users in East Lombok. The data analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of this study indicate that the Big Ramadan Sale, online customer review, and trust significantly influence on online purchase decision process, while service quality does not significantly affect on online purchase decision process in Shopee users. The trust is able to full mediation the influence of service quality and online customer review on online purchase decision process, while the trust is unable to mediation the influence of Big Ramadan Sale on online purchase decision process in Shopee users. The finding of study can be a reference for future researchers who will study similar problems related to the determining factors of the online purchasing decision process in marketplaces in Indonesia. It is hoped that the results of this research can help companies maintain transaction security and provide reviews that can strengthen consumer trust so that the online shopping decision process continues to improve.